Maternal risk factors in stunting of children aged 24-59 months - Keke Susilowati Sholehah; Endang Sutedja; Hadyana Sukandar (International Journal of Public Health Science (IJPHS), 2022)
Stunting is a height that is not appropriate with the age, it is characterized by delayed growth of the child who results in failure to reach normal height. The high prevalence of stunting in the world, 14-17% of child mortality is caused by stunting. Pandeglang Regency, Indonesia is an area with the highest prevalence of stunting in Banten Province and the prevalence is 39.5%. The purpose of this study was to analyze the maternal risk factors that the most influence prevalence of stunting in children with aged 24-59 months in Pandeglang Regency, Banten Province, Indonesia. This research is an analytic observational study with a case control study design and using 200 respondents. The case group were mothers who had stunted children and the control group were mothers who had children with normal stature. Data obtained from filling out the mother's questionnaire include maternal and child health books. The results of multivariable analysis with multiple logistic regression found that close birth spacing ORadj (95% CI): 9.61 (1.16-79.56), nutritional status of pregnant women (KEK) ORadj: 4.37 (1.79-10.64), short mother's height was ORadj L: 2.38 (1.21-4.67) and preterm gestational age was ORadj: 1.98 (1.06-3.72) and Fe minimum consumption ORadj: 1.75 (0.94-3.26). Birth spacing are the most influential maternal risk factors for the prevalence of stunting in children aged 24-59 months. Long-term contraceptive methods such as IUDs and implants need to be held to increase long-term family planning acceptors so they can be more optimal in spacing pregnancies at least two years.